Caracterização estrutural e monitoramento ótico da cristalização de nanocompósitos de polietileno de alta densidade com partículas de diferentes geometrias durante a moldagem por injeção - Beatrice, Cesar Augusto Gonçalves (2014)
The main objectives of this project were to study the morphology, the crystallization kinetics and to monitor on-line the crystallization during the injection molding process using an optical system of nanocomposites of high density polyethylene (HDPE) with three different inorganic particles: montmorillonite nanoclay, halloysite nanotubes and faujasite type zeolite. The optical system allowed analyzing the crystallization process by the changes of the optical properties during the solidification of the materials. The nanocomposites were prepared by melt intercalation in a twin-screw extruder. The resultant structures were characterized by transmission electron microscopy (TEM) and rheological properties. The extruded nanocomposites developed intercalated and well distributed structures. Crystallization kinetics studies were done by differential scanning calorimetry (DSC) and rheological measurements. It was concluded that the nanoparticles in quiescent conditions accelerated the overall crystallization of HDPE, acting as nucleating agents. The nucleating effect of these particles was predominant over the HDPE crystallization and they also modified the nucleation mechanism and the crystal morphology in some conditions. From the studies of flow induced crystallization, it was observed again that the nanoparticles accelerated the crystal growth rate. In this case it was attributed to the weak forces between the polymer chains and the surface of the nanoparticles. Finally, the nanocomposites’ crystallization was monitored during the injection molding process. The optical system showed that the nanoparticles accelerated the crystallization of HDPE; the optical results were correlated with the morphology of the injection molded samples.